2021
DOI: 10.3390/jcm10122681
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Machine and Human Examiners for Detection of Laryngeal Penetration or Aspiration in Videofluoroscopic Swallowing Studies

Abstract: Computer-assisted analysis is expected to improve the reliability of videofluoroscopic swallowing studies (VFSSs), but its usefulness is limited. Previously, we proposed a deep learning model that can detect laryngeal penetration or aspiration fully automatically in VFSS video images, but the evidence for its reliability was insufficient. This study aims to compare the intra- and inter-rater reliability of the computer model and human raters. The test dataset consisted of 173 video files from which the existen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“… 9 , 12 , 15 , 32 As previously demonstrated, the computer vision algorithm will exhibit perfect intrarater reliability and substantial interrater reliability with human annotators regardless of the washout period. 17 Furthermore, the computer vision annotator developed herein has an advantage in efficiency once incorporated into routine practice. With exponential increase in digitization of imaging data given more sophisticated warehousing and management technologies, this tool can be leveraged for imaging annotations that are not practical for clinicians.…”
Section: Discussionmentioning
confidence: 99%
“… 9 , 12 , 15 , 32 As previously demonstrated, the computer vision algorithm will exhibit perfect intrarater reliability and substantial interrater reliability with human annotators regardless of the washout period. 17 Furthermore, the computer vision annotator developed herein has an advantage in efficiency once incorporated into routine practice. With exponential increase in digitization of imaging data given more sophisticated warehousing and management technologies, this tool can be leveraged for imaging annotations that are not practical for clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al [33] used a DL model to detect airway invasion from VFSS images, without clinician input, with 97.2% accuracy in classifying image frames and 93.2% in classifying video files. Kim et al [34] used the same DL model and found moderate to substantial inter-rater agreement between the machine and human. However, these studies highlight a pertinent limitation in the use of AI for aspiration detection.…”
Section: Detection Of Aspirationmentioning
confidence: 97%
“…However, VFSS are time-consuming to conduct and can be laborious to interpret, particularly for inexperienced clinicians. Further, VFSS interpretation is prone to human error [31,34]. DL frameworks have the potential to improve the accuracy and speed with which VFSS are interpreted, and thus, they have several clinical applications depending on the method of detection used.…”
Section: Implications For Speech-language Pathologymentioning
confidence: 99%
See 1 more Smart Citation
“…A reliability study by Kim et al [2] confirmed that computer analysis using a deep learning model could detect laryngeal penetration or aspiration in recordings of videofluoroscopic swallowing studies (VFSS) as reliably as human examiners. These results provide further evidence to support the clinical application of deep learning technology in addition to the visuoperceptual evaluation of videofluoroscopic and possibly endoscopic recordings of swallowing.…”
mentioning
confidence: 96%